A Kalman filter with intermittent observations and reconstruction of data losses - Rhouma, Taouba; Keller, Jean Yves; Abdelkrim, Mohamed Naceur (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with the problem of joint state and unknown input estimation for stochastic discrete-time linear systems subject to intermittent unknown inputs on measurements. A Kalman filter approach is proposed for state prediction and intermittent unknown input reconstruction. The filter design is based on the minimization of the trace of the state estimation error covariance matrix under the constraint that the state prediction error is decoupled from active unknown inputs corrupting measurements at the current time.
Keywords: Kalman filters; intermittent unknown inputs; linear systems; intermittent observation